Determination of Gender From Facial Angels - Kosif, Rengin; Kürkçüoğlu, Ayla (The Bulletin of Legal Medicine, 2022)
Objective: There are measurement studies using different techniques on different ethnic origins in many countries, aimed at revealing the differences between the genders, from the determined anthropometric points for the eye, nose, lips, and mouth contours, which form the main lines of the face. In this study, we aimed to determine the role of facial angles in gender prediction, which is less common in the literature. Methods: In this study, 126 male and 121 female volunteers aged between 18-25 participated. Lateral photogrammetric images of all participants were taken in a natural head position, mouth in normal position, upper and lower lips closed to contact, and all images were transferred to the computer environment. Six anthropometric points determined in the vertical plane and three angles between these points were measured by the same researcher on all photographs. Results: The nasofrontal angle was found to be statistically significantly larger in women than in men (p=0,000). The differential diagnosis reliability of the nasofrontal angle was found to be very strong. While statistically no significant difference was found between nasolabial angle values, a statistically significant difference was found between genders in terms of mentolabial angle values ​​(p=0,022). The mentolabial angle was significantly larger in women and the differential diagnosis reliability was determined as strong. Conclusion: We think that the results obtained in our study will contribute to departments such as anatomy, psychiatry, human resources departments, information technology, forensic medicine, which are interested in facial analysis.